Physical Fitness in Austrian Elementary School Children Prior to and Post-Covid-19 - De Moraes-Ferrari, G (American Institute of Mathematical Sciences, 2023)
Background: With the emergence of the COVID-19 pandemic, many countries implemented policies that included movement restrictions, social distancing and school closures in order to control the spread of the virus. Even though these actions may have been necessary to save lives, there have been some unintended consequences that could affect future public health. Methods: The present study uses data from more than 24,500 Austrian elementary school children (51.2% male) that participated in a state-wide fitness evaluation program, which was initiated in the 2016/17 school year. In addition to body weight and height, data on cardiorespiratory endurance, muscular power, speed, agility, flexibility and object control were collected from three cohorts prior to the implementation of movement restrictions (school years: 2016/17, 2017/18, 2018/19) and one cohort in 2022, after the majority of COVID-19 policies had been lifted. Results: Body mass index percentiles were significantly higher in children post-COVID-19 (p < 0.01). Further, cardiorespiratory endurance, agility and flexibility were significantly lower post-COVID-19 compared to the years preceding movement restrictions (p ≤ 0.01), while absolute muscular strength was higher in the year 2022 (p < 0.01). Conclusion: Given the detrimental effects of COVID-19 policies on physical fitness in children, additional efforts are necessary that include versatile opportunities for physical activity and the promotion of physical fitness in order to modify the observed negative health trajectories and ensure future public health. © 2023 The authors.